Martian meteorites as windows into planetary volcanism: insights from olivine-phyric shergottite meteorites - Peel, Chad (Department of Geological Sciences, 2025)
Martian meteorites are the only samples currently available from the surface of Mars to study in terrestrial laboratories and can provide valuable insight into magmatic processes and the planet's geological evolution. With more meteorites being found every year, researchers no longer need to look only at single meteorites but rather groups, paired based on their crystallisation ages, ejection ages, and geochemistry. This allows for the development of models of volcanism using suites of meteorites, rather than relying solely on single meteorites. One group of shergottite meteorites, comprising approximately 20 samples with crystallisation ages from 2.4 to 0.35 Ga, share similar geochemical characteristics and ejection ages of 1.1 Ma, and are suggested to have originated from a common long-lived volcanic system. Thus, by studying these 1.1 Ma ejection paired meteorites, it is now possible to evaluate martian magma plumbing systems through time. In chapter 2, I present a comprehensive investigation of two 1.1 Ma ejection-paired olivine-phyric shergottites, Northwest Africa (NWA) 2046 and NWA 4925. I show that Mg-rich olivine megacrysts in both samples represent phenocrysts and evidence of early olivine fractionation in staging chambers prior to ascent to surface. Distinct patterns of terrestrial alteration, notably in NWA 4925, have been identified through Ca and K elemental mapping, manifesting in the preferential alteration of olivine megacryst cores and LREE enrichment of bulk-rock and pyroxene. Analysis of 87Sr/86Sr in maskelynite and low fO2 crystallisation conditions suggest a shared mantle source region with other 1.1 Ma ejection-paired samples, particularly the ~470 Ma DaG 476, SaU 005, and Yamato 980459, while pressure estimates using pyroxene Ti/Ai ratios, indicate common or multiple staging chambers near the base of the crust. In this chapter, I combine my data with literature data for other 1.1 Ma shergottites (e.g., DaG 476, SaU 005, and Yamato 980459) to present a model for volcanism at this site. One of the other major unanswered questions in the study of martian meteorites is the origin of the enriched geochemical reservoir on Mars, as either a distinct mantle source or crust. Olivine-phyric shergottites, the most primitive type of martian meteorite, are commonly interpreted to represent primary mantle derived melts, and can be categorised into three distinct geochemical groups, incompatible-trace element depleted, intermediate, and enriched, reflecting distinct source reservoirs. The primary focus of remaining chapters (3 and 4) of this dissertation is to track the evolution of REEs in these rocks from the start of crystallisation to the end. This was carried out using a newly developed laser ablation ICP-MS technique with enhanced sensitivity to analyse REEs in olivine as a proxy for the initial parent melt. The REEs of olivine-hosted melt inclusion glass and late-stage merrillite from the same samples were then measured for comparison against olivine. By comparing these, I can robustly constrain the REE evolution of shergottite parent melts and evaluate the possibility of crustal assimilation or open system processes during evolution. To do this, in chapter 3 I present the first full REE dataset for Mg-rich olivine in shergottites in a comprehensive suite of depleted, intermediate, and enriched olivine-phyric shergottites (11 samples) including: Dar Al Gani (DaG) 1037, NWA 2046, 4925, 6234, 10170, 1068, 1183, Dhofar (Dho) 019, Sayh al Uhaymir (SaU) 005, Tissint, and Larkman Nunatak (LAR) 12011. In chapter 4, I combine the olivine REE findings of chapter 3 with melt inclusion glass and merrillite data to fully evaluate the REE evolution of shergottite melts. In chapter 3, my analysis of early formed olivine megacryst trace element and ultra-trace element compositions in depleted shergottites indicates closed-system crystallisation behaviour, supporting interpretations that these meteorites represent partial melting of a LREE depleted mantle source. Olivine in the enriched shergottite LAR 12011 are LREE-depleted and identical to the REE pattens of olivine in depleted shergottites. This suggests open-system behaviour, potentially involving assimilation of xenocrystic LREE-depleted olivine or mixing with a LREE-enriched melt. Olivines in the enriched shergottite NWA 1183 are LREE enriched compared to NWA 1068 and LAR 06319 and points towards open system processes such as magma mixing and/or crustal assimilation. In chapter 4, I evaluate the use of olivine-hosted melt inclusion glass in constraining primary REE patterns for shergottites. My findings show that the REE patterns of melt inclusion glass parallel that of bulk-rock, which indicates that glass is useful in constraining REE contents of early melts trapped in olivine. The REE patterns for melt inclusion glass in the depleted shergottites also parallel REE patterns for Mg-rich olivine and later-crystallising merrillite, indicating closed-system behaviour during crystallisation and consistent with my findings of chapter 3. Intermediate shergottites NWA 6234 and NWA 10170 also exhibit closed-system behaviour, indicating partial melting from distinct mantle source regions. For LAR 12011, distinct LREE-depleted and LREE-enriched melt inclusion glass populations were observed in LREE-depleted olivine megacrysts previously analysed in chapter 3, with depleted glasses hosted in olivine megacryst core regions (Fo68 to Fo75) and LREE-enriched glasses in olivine core-mantle regions (Fo69 to Fo73). These findings suggest that olivine megacryst cores from LAR 12011 appear to have crystallised from a depleted melt rather than an enriched melt. Melt inclusion glass of NWA 1183 shows LREE enrichment attributed to assimilation of an enriched crustal component, akin to processes observed in NWA 7034, before any crystallisation had occurred.